The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3892/or.2013.2328
|View full text |Cite
|
Sign up to set email alerts
|

Core binding factor acute myeloid leukaemia and c-KIT mutations

Abstract: Abstract. Core binding factor (CBF) acute myeloid leukaemia (AML) represents 5-8% of all AMLs and has a relatively favourable prognosis. However, activating c-KIT mutations are reported to be associated with higher risk of relapse and shorter survival. To verify the incidence and prognostic value of c-KIT mutations in CBF AML, we retrospectively analysed bone marrow samples of 23 consecutive adult patients with de novo CBF AML [14 inv(16) and 9 t(8;21)] treated at a single institution from 2000 to 2011. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 23 publications
1
25
1
2
Order By: Relevance
“…The Hsp90 client proteins Akt and c-Kit, involved in autophagy regulation and prosurvival signaling, respectively, might be relevant in t(8;21) AML because ;50% of AML patients show constitutive activation of the phosphatidylinositol 3-kinase/Akt pathway, 40 and activating c-Kit mutations mediating cellular survival are predominantly found in t(8;21) and inv(16) AML subtypes. 41,42 The regulation of autophagy and survival may be tightly linked, as loss of survival signals, which would mimic growth factor starvation, is known to induce autophagy. 43 It will be interesting in future studies to elucidate whether nonhistone targets 5 mM) in the absence or presence of CQ for 16 hours, 800 cells were seeded in Methocult medium in the absence of drugs, and colonies were scored 8 days later.…”
Section: Discussionmentioning
confidence: 99%
“…The Hsp90 client proteins Akt and c-Kit, involved in autophagy regulation and prosurvival signaling, respectively, might be relevant in t(8;21) AML because ;50% of AML patients show constitutive activation of the phosphatidylinositol 3-kinase/Akt pathway, 40 and activating c-Kit mutations mediating cellular survival are predominantly found in t(8;21) and inv(16) AML subtypes. 41,42 The regulation of autophagy and survival may be tightly linked, as loss of survival signals, which would mimic growth factor starvation, is known to induce autophagy. 43 It will be interesting in future studies to elucidate whether nonhistone targets 5 mM) in the absence or presence of CQ for 16 hours, 800 cells were seeded in Methocult medium in the absence of drugs, and colonies were scored 8 days later.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a lowest level of miR-196b in patient with C-Kit mutation compared with others. Earlier studies have found that C-Kit mutation is associated with unfavorable prognosis of adult AML with t (8; 21) ( Boissel et al, 2006[2]), and AML children with t (8;21) or CBF-rearrangement (Shimada et al, 2006[28]; Manara et al, 2014[17]), yet other investigations indicated that no significant relevance existed between C-Kit mutation and the prognosis of AML children and adults (Pollard et al, 2010[23]; Goemans et al, 2005[9]; Shih et al, 2008[27]; Riera et al, 2013[26]). As is mentioned before, we forcefully demonstrated the prognostic relevance of low miR-196b expression to favorable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Эта мутация не-однократно описана у больных ОМЛ с характерными изменениями хромосом, а именно с t(8;21)(q22;q22) и inv(16)/t(16;16)(q13;q22) [106,107]. Эти изменения хро-мосом объединяются в одну группу, т. к. при них повреж-даются гены, кодирующие субъединицы фактора CBF, и характеризуются благоприятным прогнозом заболевания.…”
Section: мутации гена Kitunclassified
“…Прогноз заболевания в данном случае зависит от типа мутации, а также от варианта хромосомной патологии и возраста пациента [106,110]. В противоположность такому мнению есть единичные сообщения о независи-мости прогноза CBF-ассоциированного ОМЛ от наличия мутации KIT [107]. Кроме того, во многих исследованиях показано, что присутствие мутации KIT свидетельствует о плохом прогнозе заболевания у больных с t(8;21), но не с inv(16)/t(16;16) [108,[111][112][113].…”
Section: мутации гена Kitunclassified